Factors influencing incidence of red spider mite of tea, Oligonychus coffeae (Nietner) in Assam (The Journal of Plant Protection Sciences, 2024)
During the experimental period all data on meteorological factors viz., temperature (maximum and minimum),  relative humidity, total rainfall and bright sunshine hours were collected for the entire period of study from the  Department of Agrometeorology, AAU, Jorhat.The incidence of red spider mite, Oligonychus coffeae on tea leaves  was maximum during month of April to May-June and September-October (2011). The minimum number of mites  was recorded from July- August and November (2011) to February (2012). The data taken from 1st week of April,  2011 to last week of March 2012. In case of eggs population, there was a gradual increasing trend in egg number to  reach the peak population in the month of April. From April to June overall higher population of eggs/leaf was  noticed. Afterwards sharp decline in number of eggs was noticed during July and August. Again population of  eggs was increased during September and October. Very minimum population of eggs was observed from Novem ber to January. Population of eggs was started increasing again from 1st week of February to March. Results of the  present studies showed that the buildup of the red spider mite, O. coffeae population, as well as the number of eggs  had a significantly positive correlation with the maximum temperature(r=0.320 and r=0.286 for the mites and eggs,  respectively) and minimum temperature (r=0.268 and r=0.279 for mites and eggs, respectively). Whereas the motile stage of red spider mite, O. coffeae and eggs had a negative and significant correlation with average relative  humidity (r = -0.357 and r = -0.282 for mites and eggs, respectively).
Keywords: Red spider mite; Oligonychus coffeae; incidence; meteorological factors